Incongruous Names: the Humorous Coinage and Use of Proper Names - Manon Philippe (Lexis: Journal in English Lexicology)
This paper analyses how proper names fit in the incongruity resolution theory of humor, more specifically Bergson (1911)’s theory of humor as rigidification (and related distraction and exaggeration). The relevant properties of proper names, such as their rigid format and semantic unanalysability, their high degree of lexicalization, and their potential role as parangons, are explained in order to suggest possible metalinguistic script oppositions that could describe how proper names, as lexical units, are used in humorous contexts.